Two factor authentication for web based system using graphical password approach / Noraini Md Shaffi - Md Shaffi, Noraini (2020)
Nowadays, many people have a problem using a traditional password which is commonly a text base password. This authentication method is proven to have several weaknesses. For example, the user that uses text-based methods has low privacy security where the user generally tends to select the password that is easier to remember and that gives rise to the password. This project aims to design Two factor authentication for Web Based systems using Text-based and Graphical password approach. This project was split into 5 phases: Planning, Literature Review, Requirement Gathering and Analysis, System Design and System Development. The users for this project will be people who want to secure their things, data on websites. Users will manage their data properly using this two-factor authentication project. Graphical password is one of several techniques that can secure the password. The requirement for this project was gathered by article and journal. This Graphical password also When this system was in testing phase, two students from Faculty Science Computer and Mathematics will test the system for effectiveness.